(3GdGfOeGL GdeUQaj (B:s (3GdOhGaY hGdGfYcGSGJ (B/s - (3bhGd, RhGhjI EjeGfs ((3GdLRGFQ (B: s (3OGQ EjdjGA ddfTQ hGdJhRjY(B, s, 2024)
(3GdGfOeGL GdeUQaj h eSDhdjI GJNGP GdbQGQ , YdGbI GdGfOeGL GdeUQaj HGdbOQI GdJfGaSjI , eYjGQ caGjI QGS GdeGd h NUNUI GdHfhc ,GfYcGSGJ GdGfOeGL GdeUQaj Ydi GOGA GdefXheI GdHfcjI (B.s
(3eQGLY U(B.145-147s
Keywords: (3GdHfhcs; (3GdUjGQaIs